POLYCYSTIC OVARY SYNDROME (PCOS) IN YOUNG WOMEN: NEW TRENDS IN DIAGNOSIS AND MANAGEMENT - Kamoljonova Go‘zaloy Odiljon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Polycystic Ovary Syndrome (PCOS) is one of the most prevalent endocrine disorders among young women of reproductive age. Diagnostic criteria and therapeutic approaches have evolved in recent years, driven by advances in imaging, hormonal assessment, and lifestyle medicine. This article aims to review recent developments in the diagnosis and management of PCOS, with a focus on early detection and personalised interventions.